# Why does Mathematica not simplify this expression?

Consider this simple example:

mytrans[expr_] :=
expr /. Ω1^2 + Δ^2 :> Ω^2

f =
FullSimplify[Sqrt[-Δ^2 - Ω1^2],
TransformationFunctions -> {Automatic, mytrans}, Assumptions -> #] &;

f /@ {{Δ > 0, Ω1 > 0, Ω > 0},
{Δ > 0, Ω1 < 0, Ω > 0},
{Δ < 0, Ω1 > 0, Ω > 0},
{Δ < 0, Ω1 < 0, Ω > 0},
{Δ ∈ Reals, Ω1 ∈ Reals, Ω > 0}}

(* {I Ω, I Ω, I Ω, I Ω, Sqrt[-Δ^2 - Ω1^2]} *)


Isn't the last assumption equivalent to the first four? Why doesn't it work? Or why does it work in the first four cases?

Firstly, let's see this case:

In:= (FullSimplify[Sqrt[-a^2 - b^2],
Assumptions -> #] &) /@ {{a > 0, b > 0, c > 0}, {a > 0, b < 0,
c > 0}, {a < 0, b > 0, c > 0}, {a < 0, b < 0,
c > 0}, {a ∈ Reals, b ∈ Reals, c > 0}}

Out= {I Sqrt[a^2 + b^2], I Sqrt[a^2 + b^2], I Sqrt[a^2 + b^2],
I Sqrt[a^2 + b^2], Sqrt[-a^2 - b^2]}


In the last assumption, $\sqrt{-a^2-b^2}$ isn't simplified. It seems that for some unknown reasons, FullSimplify doesn't work in this case, though Resolve can give the correct answer.

In:= FullSimplify[Sqrt[-(a^2 + b^2)] == I Sqrt[a^2 + b^2],
Assumptions -> {a, b} ∈ Reals]

Out= Sqrt[-a^2 - b^2] == I Sqrt[a^2 + b^2]

In:= Resolve[
ForAll[{a, b}, {a, b} ∈ Reals,
Sqrt[-a^2 - b^2] == I Sqrt[a^2 + b^2]]]

Out= True


Then let's see this

In:= Sqrt[-a-b]/.a+b:>c
Out= Sqrt[-a-b]
In:= HoldForm[Sqrt[-a-b]/.a+b:>c]//FullForm
Out//FullForm= HoldForm[ReplaceAll[Power[Plus[Times[-1,a],Times[-1,b]],Rational[1,2]],RuleDelayed[Plus[a,b],c]]]


The FullForm shows that $\sqrt{-a-b}$ is Plus[Times[-1,a],Times[-1,b]], while $\sqrt{a+b}$ is Plus[a,b], they don't match, so the ReplaceAll doesn't work

To avoid this case, we can use a->c-b as the rule, and it will be OK

In:= Sqrt[-a - b] /. a :> c - b

Out= Sqrt[-c]


Now we can return you problem, change mytrans in this way, and the answer will be correct

mytrans[expr_] :=
expr /. Ω1^2 :> Ω^2 - Δ^2

f =
FullSimplify[Sqrt[-Δ^2 - Ω1^2],
TransformationFunctions -> {Automatic, mytrans}, Assumptions -> #] &;

f /@ {{Δ > 0, Ω1 > 0, Ω > 0},
{Δ > 0, Ω1 < 0, Ω > 0},
{Δ < 0, Ω1 > 0, Ω > 0},
{Δ < 0, Ω1 < 0, Ω > 0},
{Δ ∈ Reals, Ω1 ∈ Reals, Ω > 0}}

(* {I Ω, I Ω, I Ω, I Ω, I Ω} *)

• Why does it work if we have assumptions like a>0 b>0? For example, this works:mytrans[expr_] := expr /. a + b :> c FullSimplify[Sqrt[-a - b], TransformationFunctions -> {Automatic, mytrans}, Assumptions -> {c > 0, a > 0, b > 0}] – xslittlegrass Sep 5 '14 at 4:10
• Because FullSimplify[Sqrt[-a - b], Assumptions -> { a > 0, b > 0}] give the result $i \sqrt{a+b}$, so mytrans can work. But I don't know why it will give different result with Assumptions -> {a, b} ∈ Reals, even Assumptions -> {a >=0 , b>= 0} can't give $i \sqrt{a+b}$. That really confuse me a lont – wuyingddg Sep 5 '14 at 8:08